The effect of gestational age and cervical length measurements in the prediction of spontaneous preterm birth in twin pregnancies: an individual patient level meta‐analysis. (1st September 2015) - Kindinger, LM; Poon, LC; Cacciatore, S; MacIntyre, DA; Fox, NS; Schuit, E; Mol, BW; Liem, S; Lim, AC; Serra, V; Perales, A; Hermans, F; et al.
Abstract : Objective: To assess the effect of gestational age (GA) and cervical length (CL) measurements at transvaginal ultrasound (TVUS) in the prediction of preterm birth in twin pregnancy. Design: Individual patient data (IPD) meta‐analysis. Setting: International multicentre study. Population: Asymptomatic twin pregnancy. Methods: MEDLINE and EMBASE searches were performed and IPD obtained from authors of relevant studies. Multinomial logistic regression analysis determined probabilities for birth at ≤28 +0, 28 +1 to 32 +0, 32 +1 to 36 +0, and ≥36 +1  weeks as a function of GA at screening and CL measurements. Main outcome measures: Predicted probabilities for preterm birth at ≤28 +0, 28 +1 to 32 +0, and 32 +1 to 36 +0 . Results: A total of 6188 CL measurements were performed on 4409 twin pregnancies in 12 studies. Both GA at screening and CL had a significant and non‐linear effect on GA at birth. The best prediction of birth at ≤28 +0  weeks was provided by screening at ≤18 +0  weeks ( P  < 0.001), whereas the best prediction of birth between 28 +1 and 36 +0  weeks was provided by screening at ≥24 +0  weeks ( P  < 0.001). Negative prediction value of 100% for birth at ≤28 +0  weeks is achieved at CL 65 mm and 43 mm at ultrasound GA at ≤18 +0  weeks and at 22 +1 to 24 +0  weeks, respectively. Conclusion: In twin pregnancies, prediction of preterm birth depends on both CL and the GA at screening. When CL is <30 mm, screening at ≤18 +0  weeks is most predictive for birth at ≤28 +0  weeks. Later screening at >22 +0  weeks is most predictive of delivery at 28 +1 to 36 +0  weeks. In twins, we recommend CL screening in twins to commence from ≤18 +0  weeks. Tweetable abstract: An individual patient meta‐analysis assessing gestation and CL in the prediction of preterm birth in twins. Tweetable abstract: An individual patient meta‐analysis assessing gestation and CL in the prediction of preterm birth in twins.